2021
DOI: 10.1136/archdischild-2021-322757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic dextrose gel on the neonatal gut microbiome

Abstract: ObjectiveTo determine the effect of prophylactic dextrose gel on the infant gut microbiome.DesignObservational cohort study nested in a randomised trial.SettingThree maternity hospitals in New Zealand.PatientsInfants at risk of neonatal hypoglycaemia whose parents consented to participation in the hypoglycaemia Prevention in newborns with Oral Dextrose trial (hPOD). Infants were randomised to receive prophylactic dextrose gel or placebo gel, or were not randomised and received no gel (controls). Stool samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Its use has also been shown not to alter the neonatal gut microbiome. (11) Despite this, there is limited evidence on the use of dextrose gel as a preventive measure to reduce the incidence of hypoglycemia and subsequent admission to the NICU. A dose-nding study by Hegarty et al (The Pre-hPOD study) in 2016 concluded that 40% dextrose gel at a dose of 200 mg/kg (0.5 ml/kg) administered before the initial feed effectively reduced the incidence of hypoglycemia in the at-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…Its use has also been shown not to alter the neonatal gut microbiome. (11) Despite this, there is limited evidence on the use of dextrose gel as a preventive measure to reduce the incidence of hypoglycemia and subsequent admission to the NICU. A dose-nding study by Hegarty et al (The Pre-hPOD study) in 2016 concluded that 40% dextrose gel at a dose of 200 mg/kg (0.5 ml/kg) administered before the initial feed effectively reduced the incidence of hypoglycemia in the at-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal hypoglycaemia is the most common metabolic condition in newborns [ 2 ], causing significant long-term disability, seizures and death which is largely preventable [ 3 – 7 ]. Since this statement from the WHO, there has been considerable research in high and upper-middle income countries (HUMIC) advancing knowledge surrounding the prevention, treatment and management of neonatal hypoglycaemia [ 8 – 12 ]. This has changed clinical practice for millions of babies and families in such countries.…”
Section: Introductionmentioning
confidence: 99%